Diaporthe foeniculina and D. eres, in addition to D. ampelina, may cause Phomopsis cane and leaf spot disease in grapevine - Fedele, Giorgia; Armengol, Josep; Caffi, Tito; Languasco, Luca; Latinovic, Nedeljko; Latinovic, Jelena; León, Maela; Marchi, Guido; Mugnai, Laura; Rossi, Vittorio (Frontiers in Plant Science, 2024)
Phomopsis cane and leaf spot (PCLS) disease, affecting grapevines (Vitis vinifera and Vitis spp.), has been historically associated with Diaporthe ampelina. Typical disease symptoms, comprising bleaching and black pycnidia, have also been associated with other Diaporthe spp. In this study, we conducted a molecular identification of the Diaporthe isolates isolated from grapevine canes from different geographic areas of southern Europe showing PCLS symptoms. Then, we investigated their morphological characteristics (including mycelium growth and production of pycnidia and alpha and beta conidia) in response to temperature. Finally, we artificially inoculated grapevine shoots and leaves with a subset of these isolates. Based on our results, PCLS etiology should be reconsidered. Though D. ampelina was the most crucial causal agent of PCLS, D. eres and D. foeniculina were also pathogenic when inoculated on green shoots and leaves of grapevines. However, D. rudis was not pathogenic. Compared to D. ampelina, D. eres and D. foeniculina produced both pycnidia and alpha conidia at lower temperatures. Thus, the range of environmental conditions favorable for PCLS development needs to be widened. Our findings warrant further validation by future studies aimed at ascertaining whether the differences in temperature requirements among species are also valid for conidia-mediated infection since it could have substantial practical implications in PCLS management.